2021
DOI: 10.3389/fonc.2021.706668
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent Effects of Set7/9 Lysine Methyltransferase on Metabolism of Non-Small Cell Lung Cancer Cells

Abstract: Set7/9 is a lysine-specific methyltransferase, which regulates the functioning of both the histone and non-histone substrates, thereby significantly affecting the global gene expression landscape. Using microarray expression profiling, we have identified several key master regulators of metabolic networks, including c-Myc, that were affected by Set7/9 status. Consistent with this observation, c-Myc transcriptional targets—genes encoding the glycolytic enzymes hexokinase (HK2), aldolase (ALDOB), and lactate deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In line with this, we have recently showed that the genetic suppression of Set7/9 has led to the upregulation and activation of Hif1a and its target glycolytic genes even under normoxic conditions. Set7/9 inhibition increased the level of glycolysis and subsequent reduction of ROS accumulation in human lung cancer cells [107]. Thus, collectively, it can be concluded that Set7/9 antagonizes Hif1 activity both under normoxic and hypoxic conditions.…”
Section: Set7/9 and Ros/hif1a Pathwaymentioning
confidence: 78%
“…In line with this, we have recently showed that the genetic suppression of Set7/9 has led to the upregulation and activation of Hif1a and its target glycolytic genes even under normoxic conditions. Set7/9 inhibition increased the level of glycolysis and subsequent reduction of ROS accumulation in human lung cancer cells [107]. Thus, collectively, it can be concluded that Set7/9 antagonizes Hif1 activity both under normoxic and hypoxic conditions.…”
Section: Set7/9 and Ros/hif1a Pathwaymentioning
confidence: 78%
“…Different oncogenes and oncosupressors have a critical impact on these metabolic pathways [ 20 , 40 , 46 , 47 , 75 , 76 ]. Transcription factors c-Myc and ATF4 are two master-regulators of glycolysis, respiration, and one-carbon metabolism [ 44 , 45 , 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, along with p53 positive regulation, Set7/9 was shown to interact with and stabilize the main p53 negative regulator, Mdm2, under genotoxic conditions [ 104 ]. Moreover, our research group recently demonstrated that Set7/9 acts as a suppressor of metabolic functions of c-Myc thereby participating in the regulation of glycolysis in lung cancer cells [ 105 ]. Given that glycolysis is critical for the maintenance of stem cells [ 106 ] and Set7/9 attenuates the expression of c-Myc, the key glycolytic transcription factor, makes it plausible that Set7/9 regulates stem cells via controlling the p53-c-Myc crosstalk (Fig.…”
Section: Stemness-associated Non-histone Targets Of Set7/9mentioning
confidence: 99%